Implementasi Karakter Tanggung Jawab Siswa dalam Penguatan Asesmen Nasional Melalui Rapor Pendidikan di SMAN 1 Pringgabaya - Aulia, Widyatul; Mustari, Mohamad; Basariah, Basariah; Alqadri, Bagdawansyah (Jurusan Ilmu Sosial Politik, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2025)
This article aims to describe how student responsibility contributes to strengthening the national Education Report Card at SMAN 1 Pringgabaya. A qualitative descriptive approach was employed, with participants selected using purposive sampling, and data collected through observations, interviews, and document analysis. Data were analyzed using an interactive model that included data reduction, presentation, and conclusion drawing. Interview and observation guideline sheets served as references for identifying the various activities that reflect student responsibility in enhancing the national assessment. The findings indicate an average increase of 8.02% in the report card scores. Supporting factors for this improvement include: 1) competent human resources, 2) a conducive learning environment, 3) the P5 Program as a forum for character development based on Pancasila values, 4) student self-development, and 5) effective principal leadership. Conversely, challenges identified were: 1) limited IT skills among senior teachers, 2) unstable internet connections, and 3) failure to implement several programs according to the initial plan. The study is limited by its focus on a single school, so the findings may not be generalizable to other institutions with different contexts.